Put the student first: a learning environment for management education. The case of EduORG2.0 at the University of Pisa. (23rd January 2013) - Martini, Antonella; Cinque, Maria
There has been a vast debate in recent years about usage patterns of social computing and Web 2.0 tools in learning contexts. A growing number of researchers suggest that certain pedagogical approaches are best suited in these contexts, since they involve active engagement, social learning, continuous feedback, enabling students' autonomous understanding and the transfer of those skills to useful or real-life settings. In this article we present the use of a social network as part of a formal course of Management at the University of Pisa. The institutional VLE – based on Moodle – has been integrated with a student support group hosted on Ning. Problems and opportunities for using Ning have been discussed in small groups and students feedback will be reported. The shift from learning management system (course centric) to a personal learning environment (people centric) and then to personal learning network is also been discussed and a framework is provided.